Biomarkers: pros and cons of high-sensitivity assays for cardiac troponin - Giannitsis, Evangelos; Katus, Hugo (Nature reviews. Cardiology, 2012)
A 3-h algorithm using high-sensitivity assays for cardiac troponin to rule out myocardial infarction (MI) is recommended in current ESC guidelines. Whether faster rule-out algorithms can discriminate between MI and other conditions that elevate the troponin level, or be safely implemented across the whole spectrum of patient risk, is unclear.
Gesehen am 08.06.2018